Estrategia y metodología participativa del modelo ciudadanista de planificación y diseño de políticas públicas - Montañés Serrano, Manuel (Universidad Santiago de Cali, 2020)
In terms of Weberian models, the models of public policy planning and design mentioned in this text are the Technicist -in which the technical staff, as a social demiurge interpreting the world, formulates and executes public policies-, the Managerial -in which some social organizations are commodified and attend to social needs and demands in the manner of companies providing public services-, the Populist -in which associations that claim to represent socially vulnerable groups receive subsidies from public administrations- and the Citizen-minded -in which public officials, technical personnel, the associative network and the population in general participate in the design, execution, management and evaluation of public programmes and plans with which to attend synergistically to the needs and demands of the population- The latter model is framed within participatory democracies, which broaden and deepen both deliberative democracy and delegated democracy -known as representative-.